2018
DOI: 10.24052/jbrmr/v12is04/art-23
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotional intelligence on effective leadership in the military production factories (MPF) in Egypt

Abstract: Emotional intelligence is one of the most important personal trait linking to leadership in a way of assisting and developing the desired skills needed for those leaders applying effective leadership. There is a lack in the research literature related to leadership style in the Military Production Factories (MPFs) sector in Egypt. There is great attention and initiative to the reform in governmental sector in Egypt. This study considered as a baseline study for identifying the dominant leadership style in MPF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…As a result of the analysis, it was found that emotional intelligence has a positive and significant effect on self-leadership. The positive effect of emotional intelligence on leadership has been demonstrated by many studies (Shaaban, 2018;Batool, 2013;Goleman, 2011;Mills, 2009;Palmer et al, 2001). The result of this study is also consistent with the results of Alabdulbaqi et al (2019), Vann et al, (2017 and Sun (2015)'s studies.…”
Section: Discussionsupporting
confidence: 92%
“…As a result of the analysis, it was found that emotional intelligence has a positive and significant effect on self-leadership. The positive effect of emotional intelligence on leadership has been demonstrated by many studies (Shaaban, 2018;Batool, 2013;Goleman, 2011;Mills, 2009;Palmer et al, 2001). The result of this study is also consistent with the results of Alabdulbaqi et al (2019), Vann et al, (2017 and Sun (2015)'s studies.…”
Section: Discussionsupporting
confidence: 92%
“…Different studies and researchers have distinguished RL from other leadership approaches. (Pless &Maak, 2011) Pless andMaak (2011) have discussed and distinguished RL from other values-centered leadership theories like servant leadership presented by Greenleaf (2002), ethical leadership presented by Brown and Trevin'o (2006), authentic leadership presented by Luthans and Avolio (2003), and Gardner, Avolio, and Walumbwa (2005); transformational leadership presented by both Bass and Avolio (1995) and Shaaban (2018). Pless and Maak (2006) argue that the main difference between these leadership theories and RL is that it focuses on sustainable values and positive changes, environmentally and socially.…”
Section: Rl From Other Leadership Approachesmentioning
confidence: 99%
“…On the level of personality and the relationship between leaders applying the RL approach in their organisations, Pless (2007) has further noted that a values-based and thoroughgoing ethical fundamental principles-driven relationship between stakeholders and leaders are associated with a common sense of purpose and implication, which they promoted one another to advanced levels of commitment to achieve social change and maintainable values. Leaders applying this RL style have to encourage themselves and their followers to build their resilience (Shaaban & Shehata, 2019). Accordingly, the variables included in RL are a combination of personality traits, ethical leaders' values, motivations, characteristics, and achievements.…”
Section: Leaders Personal Dimensionmentioning
confidence: 99%
See 1 more Smart Citation